2018
DOI: 10.1002/jcb.27165
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of serum exosomal microRNAs as diagnostic and prognostic biomarkers for hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is the second leading cause of cancer‐related death worldwide. China accounts for over half of the new cases and deaths. Diagnostic imprecision and a lack of complimentary molecular biomarkers are partially responsible for this lack of progress. Herein, serum‐derived exosomal microRNA (miRNA) profiling was performed on 80 patients which histologically confirmed HCC and 30 normal controls. A classification of 8 exosomal miRNAs had biologically and statistically significant differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 30 publications
1
57
0
Order By: Relevance
“…Strategies to improve this efficacy deserve investigation. For example, recent studies indicated that the measurement of miR-122 from circulating exosomes may provide better diagnostic efficacy for HCC than the measurement of miR-122 in serum [37,38]. Other strategies such as using miRNA panels [39] or combining conventional diagnostic strategies with circulating miR-122 measurement [40] may also improve the diagnostic efficacy for HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Strategies to improve this efficacy deserve investigation. For example, recent studies indicated that the measurement of miR-122 from circulating exosomes may provide better diagnostic efficacy for HCC than the measurement of miR-122 in serum [37,38]. Other strategies such as using miRNA panels [39] or combining conventional diagnostic strategies with circulating miR-122 measurement [40] may also improve the diagnostic efficacy for HCC.…”
Section: Discussionmentioning
confidence: 99%
“…In the following year, Zhu et al discovered the role of miR-29a as a prognostic marker in HCC patients receiving surgical resection [35]. At present, growing body of evidence has shown the significance of miR-29a as a diagnostic/prognostic tool in HCC [41,42,47,50,55,[67][68][69][70] and alcoholic liver disease [71], as well as NAFLD. In 2017, Lopez-Riera et al identified circulating miR-29a as one predictor of miRNAs biomarker set in NAFLD patients [72].…”
Section: Mirs As Markers In Liver Diseasementioning
confidence: 99%
“…This indicates that miR-29a is involved in a variety of tumor progression processes and plays an important role in tumor growth, metastasis, apoptosis, and proliferation (19)(20)(21). As a member of the microRNA family, miR-29a has been expressed in many tumors and has a tumor suppressor effect (22)(23)(24), but its mechanism of action in liver cancer is worthy of further study.…”
Section: Introductionmentioning
confidence: 99%